Effects of immunization against an autocrine inhibitor of milk secretion in lactating goats. - Wilde, C J (1996)
1. Lactating goats were immunized against the goat's milk protein identified as a feedback inhibitor of lactation (FIL). Immunization was by three treatments during the declining stage of lactation. 2. When antibodies to FIL were consistently detected in milk (in response to the third treatment), the rate of decline in milk secretion was significantly reduced compared with sham-immunized controls. Such a response was not apparent with the first two treatments when serum but not milk titres of anti-FIL were raised. 3. When one gland of immunized goats was switched (after the third immunization) from twice- to once-daily milking, the ipsilateral decrease in the rate of milk secretion was reduced significantly compared with sham-immunized goats. 4. The results are compatible with the hypothesis that the autocrine agent FIL acts during milk accumulation as an inhibitor of milk secretion.